LARGE-SCALE BIOPHYSICAL EXPERIMENT "GELIOMED-2" - Vishnevskey, V.; Gromozova, E.; Ragoulskaya, M. (Одеські астрономічні публікації, 2014)
Results and new design of large-scale biophysical experiment "Geliomed 2" discusses.